Biomechanical Impacts of Forward Head Posture on the Respiratory Function - Kevin Triangto; Siti Chandra Widjanantie; Nury Nusdwinuringtyas (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Introduction: Forward head posture (FHP) is a very common problem among the working population. Being one of the most subconscious function in humans, respiratory function utilizes both the diaphragmand external intercostal muscles for quiet breathing. However during labored breathing, many other muscles will be recruited, and mostly these muscles have attachments in the cervical, thoracic ribcage,and even lumbar vertebrae. By the nature of attachments of these muscles on the cervical vertebra and thoracic cage, it is then plausible that FHP would affect the respiratory function. Methods: Thorough searches were done through international journals for the last ten years regarding the topic of FHP and its impacts to the respiratory biomechanics. Discussion: Previous studies have reported how prolonged FHP will result in kyphotic posture, reducing the mobility of ribcage, and modifies all respiratory muscular attachments such as sternocleidomastoids, intercostals, and to a certain extent, the diaphragm. All these result in a restrictive lung disorder, signified by reducing spirometry values, such as Forced Vital Capacity, Sniff Nasal Inspiratory Pressure, and Peak Flow Rate. Conclusion: Forward head posture disturb the respiratory biomechanics.